Pulmonary Function Disorders in Crews of Purse Seine Fishing Vessels - Manuputty, Monalisa; Matakupan, Johanna; Latuhihin, Richard (Graduate School, Universitas Brawijaya, 2025)
The working environment with chemical factors on fishing vessels is related to exhaust gases produced from the combustion process when the engine is operating. The chemical content of exhaust gases includes Carbon monoxide (CO) and particles in the form of dust. Unwittingly, exposure to these exhaust gases enters the crew's respiratory system while working and can cause lung problems. The purpose of this study was to analyze the effect of dust and CO variables, working period, and discipline in the use of masks on pulmonary function disorders in purse seine crews. This cross-sectional descriptive study began by distributing questionnaires about the working environment conditions with chemical factors and the discipline of using masks to 45 crew respondents. Then, the levels of dust and CO on the ship were checked. The lung function performance was also checked on the crews. The data obtained were analyzed using the Partial Least Square (PLS) analysis method. The results of pulmonary function examinations on crews showed that 71.62% of respondents had pulmonary function disorder. The results of data analysis based on the relationship between variables showed that dust and CO variables had a significant effect on pulmonary function disorders. Variables of working period and discipline on using masks also affect pulmonary function disorders directly or as moderator variables from dust and CO variables. Keywords: CO, Dust, Pulmonary Function Disorders, Purse seine.